Manhajiyyah Ta’lîm Tarjamah al-Qur’ân fî Kitâb al-Ḥisân: Dirâsah Taḥlîliyyah Tarbawiyyah Wifqa Nazariyyah Mâkî - Adam Nadzirul Wuqu; Arifa, Zakiyah (Jurnal Internasional Pendidikan Bahasa Arab, 2024)
Understanding the meaning of the Quran presents significant challenges for Muslims, particularly for beginners in religious studies. This study analyzes Al-Hisan textbooks, volumes 1 and 2, utilizing William Francis Mackey's framework to evaluate the effectiveness of Quran translation teaching methods. The research employs a qualitative approach, focusing on library research and direct observation to assess the content quality of the textbooks. Key findings indicate that Al-Hisan textbooks effectively meet Mackey's criteria of selection, gradation, presentation, and repetition, facilitating a structured learning process for students. The textbooks emphasize the translation of Surah Al-Baqarah, gradually introducing vocabulary and translation techniques, thereby enhancing comprehension and retention of Quranic meanings. This research contributes to the field of Quran translation teaching by providing a comprehensive analysis of Al-Hisan approach, highlighting its strengths and areas for improvement. The study suggests further exploration of practical implementations in educational settings to enhance the effectiveness of Quran translation learning among non-Arabic speakers, ultimately aiming to improve the overall understanding of the Quran within the Indonesian Muslim community.